Allelopathic potential of the leaf and seed of Pueraria javanica Benth. on the germination and growth of three selected weed species - Ismail B.S.,; Syamimi Halimshah,; Wan Juliana W. Ahmad,; Nornasuha Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Pueraria javanica Benth. is one of the most common leguminous cover crop used in oil palm plantations of Malaysia. A study was conducted to determine the allelopathic potential of this plant, using the aqueous extract, sandwich and dish-pack methods, with the seed and leaf (of P. javanica) on three bioassay weed species namely, Eleusine indica, Cyperus iria and Chromolaena odorata. The aqueous extract experiment was conducted using 0 (control), 16.7, 33.3 and 66.7 g/L of the aqueous leaf and seed extracts while the sandwich method was carried out using 10 and 50 mg of each of the donour plant parts. Meanwhile, the dish-pack method was done using four different distances (41, 58, 82 and 92 mm) away from the donour plant. All experiments were replicated five times using the complete randomized design (CRD). The leaf extract exhibited 100% reduction on the fresh weight of E. indica and C. odorata while the seed extract exhibited 100% reduction on all parameters for E. indica and on the fresh weight of C. iria at 66.7 g/L concentration. The seed and leaf at 10 and 50 mg significantly reduced the radicle length of all the bioassay species. The dish-pack experiment also showed a reduction effect on the germination percentage and seedling growth parameters of all the bioassay species. However, the reduction effect was not totally in accordance to the distance from the donor species. More studies need to be conducted to determine the type of reduction mechanism involved in the allelopathic activity especially with respect to molecular and biochemical aspects.